2020
DOI: 10.1101/2020.04.30.069237
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptional control of DNA repair networks by CDK7 regulates sensitivity to radiation in Myc-driven Medulloblastoma

Abstract: Myc-driven Medulloblastoma remains a major therapeutic challenge due to frequent metastasis and a poor 5-year survival rate. Myc gene amplification results in transcriptional dysregulation, proliferation, and survival of malignant cells. To identify therapeutic targets in Myc-amplified medulloblastoma we performed a CRISPR-Cas9 essentiality screen targeting 1140 genes annotated as the druggable genome. CDK7 was identified as a mediator of medulloblastoma tumorigenesis. Using covalent inhibitors and genetic dep… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 61 publications
(65 reference statements)
1
14
0
Order By: Relevance
“…Interestingly, our results show that CDK7 knockout also slightly increased cell apoptosis without chemotherapy (Fig. 2D and F); this may be related to the role of CDK7 in transcriptional control of DDR networks [39,40].…”
Section: Knockout Of Cdk7 Combined With Gemcitabine and Paclitaxel Ch...mentioning
confidence: 55%
See 2 more Smart Citations
“…Interestingly, our results show that CDK7 knockout also slightly increased cell apoptosis without chemotherapy (Fig. 2D and F); this may be related to the role of CDK7 in transcriptional control of DDR networks [39,40].…”
Section: Knockout Of Cdk7 Combined With Gemcitabine and Paclitaxel Ch...mentioning
confidence: 55%
“…1D), whose loss of function via specific sgRNAs led to lethality in the presence of gemcitabine and paclitaxel (Supplementary Table S4). Interestingly, CDK7 is involved in a wide spectrum of biological processes, including cell cycle regulation and DNA damage response [39]. The majority of CDK7-targeting sgRNA standardized read counts were considerably lower following treatment with gemcitabine and paclitaxel compared to non-treated cells (Fig.…”
Section: Crispr-cas9 Screening Identifies Genes Whose Deficiency Sens...mentioning
confidence: 99%
See 1 more Smart Citation
“…CDK7 has dual roles in regulation of transcription and cell division 42 . Two recent reports demonstrated that inhibition of CDK7 preferentially represses expression of genes in the DNA damage repair pathway and sensitized cancer cells to PARP inhibitor‐induced DNA damage 43 and ionizing irradiation 44 . However, our preliminary data with the same inhibitor of CDK7, THZ1, showed that inhibition of CDK7 catalytic activity did not resensitize DU145‐DxR to docetaxel (data not shown).…”
Section: Discussionmentioning
confidence: 65%
“…There is a growing body of evidence suggesting that other cyclin-dependent kinases including CDK7, CDK8, CDK9, and CDK12 may also be important for modulating the sensitivity of cancer cells to the effects of ionizing radiation (41)(42)(43). In contrast to CDK4/6 inhibitor-mediated radiosensitization in breast cancer that is primarily mediated through suppression of HR, inhibition of other CDK proteins leads to increased apoptosis, senescence, and/or inhibition of RNA Polymerase II function that leads to radiosenstization (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%